Digital food security atlas for Yemen - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
The Digital Food Security Atlas (DFSA) for Yemen expands the conventional concept of an atlas by allowing users to create their own maps in an interactive way. This innovative tool allows policymakers, analysts, researchers, and the interested public to visualize and analyze food security indicators such as physical and human geography, trade, infrastructure, agriculture, water, and health, and find patterns which can prompt ideas and generate hypotheses. This package can be viewed and queried with free and easy-to-install ArcReader software, and builds on a user-friendly interface that places a collection of interactive GIS maps linked to a relational geodatabase at users' fingertips.